Modular gardens by James C. Rose – A 1946 experiment for Ladies’ Home Journal - Anna-Maria Visilia (Agathón)
The ‘module’ is a design tool that is profoundly intertwined with design concepts such as proportions and geometry as well as globalization, sustainability, and equity. Modular theories and paradigms are limited in the landscape architecture discourse. This paper examines the ‘module’ as a design tool in the early work and theory of American landscape architect James C. Rose (1913-1991). In 1946, the Ladies’ Home Journal commissioned a series of small gardens to be photographed and published in a special issue. Rose considered this challenge as a design-build exercise to develop modular garden prototypes for small American suburban lots. Modularity was reframed in Rose’s works and was developed in an artistic way that portrays close relationship to modern and Japanese ideas on this theme. An in-depth analysis and discussion of Rose’s modular concepts offers an opportunity to delve into novel ideas and processes that can prove insightful for high-quality humane landscape production.